(untitled) - Barnes, Jennifer Lynn ([New York, N.Y.], 2025)
"Players move into the next round of the Grandest Game, where millions of dollars in prize money are on the line-and new relationships, motivations, and threats come to light"--
Keywords: Contests; Mystery and detective stories; Fiction; Riddles; Fiction; Puzzles; Fiction; Riddles; Juvenile fiction; Puzzles; Juvenile fiction; Contests; Juvenile fiction; Romance fiction; Detective and mystery fiction